HISTORICAL AND COMPREHENSIVE ECONOMIC ANALYSIS OF ECOLOGICAL SECURITY IN THE KHARKIV REGION AND ITS FUTURE IMPROVEMENT - and; and (Municipal economy of cities. Series: «Economy science», 2013)
The main approaches to ensure environmental safety in the Kharkiv region . It is shown that in the present conditions of economic transformation to a market economy in Ukraine to ensure environmental safety in the Kharkiv region does not correspond to the challenges facing the region and Ukraine ’s integration into the European structures. New content problems of ecological safety came into conflict with the old forms of presentation of environmental safety , which causes the need to reform systems to ensure environmental safety. With a modern and unified position deals with the basic tools of systems engineering process control software environmental safety in the Kharkiv region on the basis of functional systems analysis and provides specific recommendations .